Respuesta :
Answer:
f(x) × g(x)= x^4 - x^3 - 28x^2 + 16x + 192
Step-by-step explanation:
We have the function f(x) = x^2 − x − 12 and g(x) = x^2 − 16 and we need to find the multiplication of both functions.
f(x) × g(x) = ( x^2 − x − 12)(x^2 − 16) = x^4 - 16x^2 -x^3 + 16x -12x^2 + 192
Simplifying:
f(x) × g(x)= x^4 - x^3 - 28x^2 + 16x + 192
Answer: [tex]f(x)*g(x)=x^4-x^3-28x^2+16x+192[/tex]
Step-by-step explanation:
Given the function f(x) and g(x):
[tex]f(x)=x^2 - x -12\\\\g(x)= x^2 - 16[/tex]
We need to multiply them. To do this we need to remember the Product of power property, which states:
[tex](a^m)(a^n)=a^{(m+n)}[/tex]
And the multiplication of signs:
[tex](+)(+)=+\\(+)(-)=-\\(-)(-)=+[/tex]
Then:
[tex]f(x)*g(x)=(x^2 - x -12)(x^2 - 16)\\\\f(x)*g(x)=x^4-16x^2-x^3+16x-12x^2+192[/tex]
Adding like terms, we get:
[tex]f(x)*g(x)=x^4-x^3-28x^2+16x+192[/tex]